PELAKSANAAN PERJANJIAN KERJASAMA PERDAGANGAN BEBAS ASEAN - CINA (ACFTA) TAHUN 2010 DAN IMPLIKASINYA BAGI INDONESIA - Magdariza Magdariza; Delfiyanti Delfiyanti (Masalah-Masalah Hukum, 2011)
Nowadays, the development of free trade around A SEAN especially between ASEAN's nations and China through the "ASEAN - China Free Trade Agreement (ACFTA)" that started being effective on January 1, 2010. The establishment of a free trade area between ASEAN and China made rnconsidering China is a huge economic potency that the establishment of this cooperation is expected to drive economic growth in the Ase an region of countries member. Therefore, the greater opportunity for A SEAN and China is possible to expand the trade relations between the two countries. While in Indonesia the implementation of it is based on the Regulation of Financial Minister of Indonesia Republic No. 235/PMK.011/2008 about the determination of import tariffs to the framework of ASEAN-China Free Trade Area (ACFTA) in which the determination of 0% tariffs on goods have been targeted to 0% in 2010. As for there are some positive implications for the implementation of this in Indonesia is from the International standpoint, with theimplementation of ACFTAin Indonesia, providing great significance forgeostrategic and economic interests of Indonesia. From the national side, it is a challenge for Indonesia. where the fierce competition in terms of trade with other ASEAN countries and particularly with China, has made ffilndonesia to be more paid attention against the production quality and increase the creativity of the industry and entrepreneurs in producing and creating Indonesia's domestic-product that is ready to compete with other countries by providing international standard of production quality To be viewed in the long run of A CFTA implementation in Indonesia will bring benefits in the form of more smoothly investment flows, broader trade and economic scale so great that produce a rational allocation of resources and improve efficiency On the other hand, the negative implication is the application of import tax rates to zero percent has been made rnto the local industry in order to reduce the amount of production and it is caused by a flood of Chinese products and other ASEAN countries. with a cheaper price. It has also triggered the end many of the local industries including among SMEs and to "shut down" due not be able to compete with goods from China are cheaper than the local price. Actually, this happens due to the lack of human resources quality (HR) as well as the existing of Indonesian capital.